(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article examines the interpretation of the economic concept of «international logistics», investigates the feasibility of using marketing research on consumer behavior as an effective tool for diagnosing the functioning of international logistics, examines the main methods of logistics diagnostics, and substantiates the key dependencies between logistics indicators and the level of consumer satisfaction in the international environment. The purpose of the article.. Substantiation of the feasibility of using marketing research on consumer behavior as an effective tool for diagnosing the functioning of international logistics, research into the main methods of logistics diagnostics, as well as identifying key dependencies between logistics indicators and the level of consumer satisfaction in the international environment. Methods. The methodological basis of the study is standards, regulatory acts, theoretical provisions on the diagnostics of international logistics and consumer behavior research, scientific works of famous economists on the topic. The following methods were used to write the article: analysis of scientific literature, standards and regulatory documents to form the theoretical basis of the study; comparative analysis of international logistics services; expert evaluation method. Results. The study analyzed scientific works and regulatory acts on the economic content of the concepts of «international logistics» to identify the main methods of marketing research on the behavior of consumers of logistics services. It was studied that diagnostics of international logistics activities is an integral part of the strategic management of the enterprise. It allows to identify weaknesses, optimize processes and increase competitiveness in the international market. Regular monitoring and analysis of logistics processes will help enterprises adapt to changing conditions and market requirements. The key dependencies between logistics indicators and the level of consumer satisfaction in the international environment are substantiated, which help to identify problems and opportunities for improving the international logistics activities of the enterprise. Conclusions. The results of the study indicate the existence of a close relationship between logistics indicators (in particular, delivery speed, reliability of logistics operations, level of service) and the level of consumer satisfaction. The use of modern marketing research methods allows you to quickly and accurately identify problem areas in the logistics chain and adjust strategies for interacting with customers in the international market. The integration of marketing analytics into the logistics management system helps to increase the competitiveness of companies, ensure a customer–oriented approach and improve the quality of logistics services. Promising areas for further research are: studying the impact of logistics digitalization (including Big Data, IoT, AI) on changing consumer expectations.